Development of an oil free water-lubricated twin-screw air compressor. (October 2018) - Wang, Chuang; Xing, Ziwen; Chen, Wenqing; Yang, Qiaoming; He, Zhilong
Highlights: A prototype of water-lubricated screw compressor was developed. The influence of water injection mode on compressor performance was investigated. It should choose relatively high rotating speed to ensure high efficiency. To inject large water is feasible and effective to improve compressor performance. To choose proper injection mode would yield better effects of efficiency improvement. Abstract: Due to the growing need for the compressed air of higher quality, the water-lubricated twin-screw compressor with water as the only liquid in the compressor has drawn much attention to produce clean air absolutely free of oil. This paper presents an experimental study on the developed water-lubricated screw compressor to investigate the compressor performance under the influence of rotating speed, discharge pressure, water injection flowrate and water injection mode. The aim is to search proper operating parameters to achieve the power saving and efficiency improvement of the compressor. The results may provide some reference for the development and improvement on the water-lubricated air screw compressor in the future work.